2020
DOI: 10.30802/aalas-jaalas-19-000053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 3 Alcohol-based Agents for Presurgical Skin Preparation in Mice

Abstract: Appropriate aseptic technique is a crucial component of rodent survival surgery. Ease of technique, surgical space constraint, batch surgery, and cost are factors that may affect researcher compliance with appropriate aseptic technique. The first part of this study compared 3 antiseptic preparation agents with the standard triplicate application of povidone-iodine and alcohol. Euthanized mice (n = 40) were shaved on the dorsum, and culture swabs were taken for RODAC plating and bacterial identification. Shave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 25 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…A total of 9 RCTs were judged eligible and were included in this review. [11][12][13][14][15][16][17]24,25…”
Section: Quantity Of Research Availablementioning
confidence: 99%
See 3 more Smart Citations
“…A total of 9 RCTs were judged eligible and were included in this review. [11][12][13][14][15][16][17]24,25…”
Section: Quantity Of Research Availablementioning
confidence: 99%
“…The species on which aseptic protocols efficacy was studied were small animals (4 studies, 446 animals), cattle (2, 164), laboratory mice (2, 72), and horses (1,36). Surgery types included in the studies were classified as clean in 7 studies, 12,[14][15][16][17]24,25 and as mixed clean and clean contaminated in 2. 11,13 One study reported SSI incidence as a measure of aseptic protocol efficacy and did not report skin bacterial colonization.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preoperative skin preparation includes hair removal and disinfection of the surgical sites. It has been demonstrated that different disinfection methods indicated no significant differences, irrespective of depilatory agents or electric clippers depilation methods used [ 8 , 9 ]. However, in previous experiments, we have found fortuitously that mice depilated by sodium sulfide aqueous solution and scissors hair cutting methods presented some problems in the stages of wound healing.…”
Section: Introductionmentioning
confidence: 99%